Corrosion coupon evaluation under pilot‐scale CO2 capture conditions at an Australian coal‐fired power station. Issue 3 (29th May 2013) - Cousins, Ashleigh; Ilyushechkin, Alexander; Pearson, Pauline; Cottrell, Aaron; Huang, Sanger; Feron, Paul H.M.
Abstract: Corrosion is a major operational issue in amine treating plants. With the likely application of CO2 capture technologies to coal combustion flue gases, corrosion rates in gas streams containing oxygen are of interest and evaluation of potential construction materials under realistic conditions is essential. A total of 128 corrosion coupons were installed at the Tarong Post Combustion Capture (PCC) pilot plant in 8 locations during operation with 30 wt% monoethanolamine (MEA). Each corrosion test location contained 4 coupons of each type of metal (316L, 316L welded, C1018, C1018 galvanized). Coupons were installed in the pilot plant for 4296 or 5448 h; however plant operation was intermittent with actual operating times of 593 or 745 h. The highest corrosion rates were observed for carbon steel (C1018) and galvanized carbon steel (C1018 GLV) coupons located in both the absorber and stripper solvent storage tanks. C1018 GLV coupons typically showed higher rates of corrosion than C1018 coupons. C1018 coupons located in the absorber wash section also exhibited high corrosion rates, while C1018 GLV coupons in the same location did not. XRD analysis showed that the galvanized coupons in the absorber wash section retained some Zn in the corrosion scale. This could have aided their resistance to corrosion in this location. All other galvanized samples lost their zinc coating, indicating galvanizing might not be appropriate for use in CO2 capture applications. C1018 coupons in the absorber column experienced pitting. This was not seen for the galvanized coupons. In the stripping column, both the C1018 and C1018 GLV coupons showed areas of general corrosion attack. Stainless steel and welded stainless steel coupons showed no appreciable corrosion weight loss under the conditions tested. The corrosion resistance of the 316L stainless steel coupons to all environments considered here suggests it is suitable for use in all areas of amine based PCC plants. The corrosion rates measured on C1018 and C1018 GLV coupons suggest these materials would not be recommended for use in solvent storage tanks or wash sections of PCC plants. Due to intermittent use of the plant, it is unclear from these results whether C1018 or C1018 GLV would be suitable for use in the absorption/desorption columns. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd.